IMPLEMENTASI PEMBELAJARAN MITIGASI BENCANA BERBASIS KEGIATAN BERMAIN PERAN PADA ANAK USIA 5–6 TAHUN DI TK NEGERI PEMBINA PANDEGLANG - Sinta Nurlaila; Siti Khosiah; Isti Rusdiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a country with a high level of disaster risk; therefore, disaster mitigation education needs to be introduced from an early age. This study aimed to describe the implementation of disaster mitigation learning through role-playing activities for children aged 5–6 years at TK Negeri Pembina Pandeglang. This research employed a qualitative descriptive approach with a case study design. The research subjects consisted of the principal, classroom teacher, and children in Group B3 aged 5–6 years. Data were collected through observation, interviews, documentation, and field notes. Data analysis used the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that learning planning was carried out through the preparation of teaching modules based on the Merdeka Curriculum by integrating disaster mitigation materials into learning activities. The implementation of learning was conducted through role-playing and simulation activities that provided direct learning experiences for children. The results showed that most children were able to recognize basic disaster mitigation concepts, understand self-protection measures, follow teacher instructions, and actively participate in learning activities. Supporting factors included school support, teacher collaboration, parental involvement, and the availability of learning facilities and media. Inhibiting factors included differences in children's characteristics, limited learning media, and school environmental conditions that required intensive supervision. The implementation of disaster mitigation learning through role-playing activities provided meaningful learning experiences and helped improve children's disaster preparedness. Keywords: disaster mitigation, role play, disaster preparedness, early childhood education.